Tanggung Jawab Maskapai Penerbangan Perintis terhadap Kerugian atas Musnahnya Kargo Akibat Kecelakaan - Ayuningtyas, Celfilia Devi (Wacana Hukum, 2023)
The presence of innovative cargo air transportation plays a significant role in meeting the transportation needs of individuals residing in remote and underdeveloped regions, commonly referred to as 3T areas, in Indonesia. The primary objective of pioneering air transport is to mitigate the adverse effects of price disparities on the residents of the 3T region. Nevertheless, the implementation of pioneering cargo air transport has faced numerous challenges in reality, leading to a higher incidence of aviation accidents compared to commercial flights. This study aims to investigate the legal status of pioneering cargo air transport in Indonesia and subsequently ascertain the liability of pioneer airlines in relation to aviation safety and the financial consequences resulting from cargo destruction in the event of an accident. The research employed a normative juridical approach, which involved an examination of concepts and relevant regulations. The findings of the study suggest that pioneering cargo carriers possess a legal status that extends beyond their role as mere carriers in cargo transport agreements. They also maintain a legal connection with the government through contractual arrangements, which are integral to the execution of public services. Pioneer airlines, in collaboration with local governments, airport authorities, and relevant stakeholders, bear the responsibility of ensuring flight safety as a proactive measure to prevent accidents. In the event of an accident resulting in the destruction of the cargo, it is the responsibility of the airline to provide compensation to the sender. This compensation should be commensurate with the damages incurred and should adhere to the regulations governing air transportation.